Nest usurpation by a common eider toward a long-tailed duck - Isabeau Pratte; Mark Maftei; Mark L. Mallory (Polar Research, 2016)
Intraspecific and non-obligate brood parasitism and nest takeover is well documented in common eiders (Somateria mollissima borealis) nesting in the Arctic. However, we report the takeover of a long-tailed duck (Clangula hyemalis) nest by a female common eider on Nasaruvaalik Island, Nunavut, Canada. The high nesting density due to limited habitat in the region may have contributed to this seemingly risky behaviour, which provides no clear benefits to the eider.